Invited commentaryIs there a role for metformin in the ICU? - Jeschke, Marc G.; Herndon, David N. (Archives of Medical Science, 2008)
Commentary on Advantage of adjunct metformin and insulin therapy in the management of glycemia in critically ill patients. Evidence for nonoccurrence of lactic acidosis and needing to parenteral metformin Mojtaba Mojtahedzadeh, Mohammad R. Rouini, Farshad Kajbaf, Atabak Najafi, Ghazal Ansari, Afshin Gholipour, Ali R. Mofid, Mohammad Abdollahi Arch Med Sci 2008; 4, 2: 174–181